2005
DOI: 10.1007/s10450-005-5898-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Azeotropic Behavior in Adsorbed Mixtures

Abstract: An analogy between vapor adsorbed equilibrium and vapor liquid equilibrium is made to determine the condition where azeotropes are observed, using a relationship between infinite dilution activity coefficients and pure component pressures in the reference state. The range of conditions where azeotropic behavior is expected in vaporadsorbed equilibrium (VAE) was determined for the multisite Langmuir model for a mixture of two components with molecules of different size, and for CO 2 -C 3 H 8 on NaX using an emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…The resulting threeparameter expression for the excess Gibbs energy is asymmetrical in composition and has an exponential dependency upon the reduced grand potential, thus being thermodynamically consistent [4,7]. Another contribution of the current investigation is to discuss the behaviour of adsorption azeotropes in relation to the infinite dilution activity coefficients and their visualization on the reduced grand potentialcomposition diagram at constant temperature and pressure, therefore confirming and extending the conditions for azeotrope existence defined by Siperstein [12].…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…The resulting threeparameter expression for the excess Gibbs energy is asymmetrical in composition and has an exponential dependency upon the reduced grand potential, thus being thermodynamically consistent [4,7]. Another contribution of the current investigation is to discuss the behaviour of adsorption azeotropes in relation to the infinite dilution activity coefficients and their visualization on the reduced grand potentialcomposition diagram at constant temperature and pressure, therefore confirming and extending the conditions for azeotrope existence defined by Siperstein [12].…”
Section: Introductionsupporting
confidence: 78%
“…With the aim of determining the conditions where azeotropic behaviour is observed, Siperstein [12] showed that the existence of an adsorption azeotrope can be defined from relations between the infinite dilution activity coefficients and the surface pressure of the pure components at the same temperature and reduced grand potential of the mixture. In particular, these relationships can be obtained from the slope of the bubble point pressure curve while it approaches the pure component.…”
Section: Implications Of Azeotropic Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Adsorption of the carbon dioxide(1)/propane(2) binary system on zeolite 13X exhibits an azeotrope and it has been studied extensively introducing a model for the excess Gibbs energy [14]. Isotherms parameters are reported in Table 1.…”
Section: Common Tangent Approach For Non-ideal Adsorption At Low Presmentioning
confidence: 99%